2020
DOI: 10.1002/er.6099
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized Ti 4 O 7 supported on carbon nanotubes composite modified separator for enhanced electrochemical properties of lithium sulfur battery

Abstract: Summary The novel lithium sulfur (Li‐S) battery is widely concerned owing to its ultrahigh theoretical energy density of 2600 Wh/kg. However, its commercial application has been obstructed by the rapid decline of capacity and short cycle life, which is mainly because of the dissolution behavior of polysulfides into electrolyte solution and subsequently continual shuttling effect. Some strategies including carbon carriers for loading sulfur, modification of electrolyte and overall structure design of cell are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Essentially, adding MWCNTs made TiO a viable modifier for LSB separators, allowing an astoundingly low capacity fade rate of 0.057% per cycle. Similarly, recent studies combined various CNTs with oxygen-rich MnO nanoflakes, 230 TiO 2 , 231 Nb 2 O 5 , 232 MnO, 233 and Ti 4 O 7 234 to enhance specific capacity while also significantly improving polysulfide rejection. Wang et al 235 sandwiched 1D SWCNTs between 2D V 2 C/V 2 O 5 nanosheet layers to prevent the nanosheets from agglomerating, resulting in a maximum number of active sites for polysulfide adsorption.…”
Section: Carbon-based Modificationsmentioning
confidence: 99%
“…Essentially, adding MWCNTs made TiO a viable modifier for LSB separators, allowing an astoundingly low capacity fade rate of 0.057% per cycle. Similarly, recent studies combined various CNTs with oxygen-rich MnO nanoflakes, 230 TiO 2 , 231 Nb 2 O 5 , 232 MnO, 233 and Ti 4 O 7 234 to enhance specific capacity while also significantly improving polysulfide rejection. Wang et al 235 sandwiched 1D SWCNTs between 2D V 2 C/V 2 O 5 nanosheet layers to prevent the nanosheets from agglomerating, resulting in a maximum number of active sites for polysulfide adsorption.…”
Section: Carbon-based Modificationsmentioning
confidence: 99%
“…In contrast, polar materials, such as transition metal oxides, help in efficiently immobilizing LiPSs and promoting their conversion. In recent years, some reports have shown that metal oxides of inorganic polar compounds, such as TiO 2 , 12 Ti 4 O 7 , 13 V 2 O 5 , 14 MnO 2 , 15 and SnO 2 , 16 can efficiently inhibit the shuttle effect benefiting from the ability to effectively trap LiPSs through strong chemical interactions. However, the conductivity of these polar compounds is generally lower than that of carbon materials, resulting in low sulfur utilization and poor rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Recently, a variety of functional materials have been applied to modify the separators of Li–S batteries. 20–22 It has been reported that polar transition metal oxides (TMOs), such as Co 3 O 4 , 23 Nb 2 O 5 , 24 NiO, 25 Ti 4 O 7 , 26 oxygen-deficient TiO 2 , 27 TiO, 28 and ZnO, 29 can effectively anchor LiPSs and even promote the redox kinetics of LiPSs. Among these TMOs, CoO has gained great attention due to its strong chemical adsorption to LiPSs.…”
Section: Introductionmentioning
confidence: 99%